tingkat partisipasi pemilih suku samin dalam pilkada serentak kabupaten pati tahun 2017 - wahid abdulrahman; muhammad Adnan (Journal of Politic and Government Studies, 2018)
ABSTRACTThe skeptical and reluctant attitude of Samin Tribe in public participation has become their identical signature. However, during the last regional election in District of Pati most of the Samin Tribe registered as DPT cast their vote. The possibility of the ongoing problem with the cement factory influencing this political participation of the Samin Tribe is the background of this research with the main questions; how was the level of voter participation conducted of the Samin Tribe during the Regional Election of Pati in 2017? What is the connection between the cement factory issue with the regional election for the Samin Tribe? The purpose of this research is to describe the level of voter participation of Samin Tribe during the regional election of Pati in 2017. Other than that this research also attempt to find out and explain whether the ongoing problem with the cement factory will have something to do with the election or not. The theory used in this research is the political participation in describing the level by using stratified random sampling mode. The object of the research is the Samin Tribe who are registered as DPT the Regional Election of Pati in 2017. The result of the research shows 66, 7% of Samin Tribe uses their rights to vote while 33, 3% of them choose to abstain (golput). From these result indicate that the participation rate of samin tribe voters is included in active political participation, but it also found out there is no correlation between the cement factory issue and the regional election for the Samin Tribe. The Samin Tribe to be more open willing to participate in political participation without abandoning their teachings from their belief and still maintain a good level of participation in every election. The Samin Tribe should also be more assertive towards those who used their tribe’s name for particular interest. Key words: Political Participation, Samin Tribe, Regional Election, Cement Factory Issue